Interferometric system based on swept source optical coherence tomography scheme applied to the measurement of distances of industrial interest - Morel, Eneas Nicolas (2016)
We used an interferometric technique based on typical optical coherence tomography (OCT) schemes for measuring distances of industrial interest. The system employed as a light source a tunable erbium-doped fiber laser of ∼20-pm bandwidth with a tuning range between 1520 and 1570 nm. It has a sufficientlylong coherence length to enable long depth range imaging. A set of fiber Bragg gratings was used as a self-calibration method, which has the advantage of being a passive system that requires no additional electronic devices. The proposed configuration and the coherence length of the laser enlarge the range of maximumdistances that can be measured with the common OCT configuration, maintaining a good axial resolution. A measuring range slightly >17 cm was determined. The system performance was evaluated by studying the repeatability and axial resolution of the results when the same optical path difference was measured.Additionally, the thickness of a semitransparent medium was also measured.